The Effect Of Tax Avoidance, Profitability, And Firm Size On Firm Value (Case Study Of Pharmaceutical Companies Listed On The IDX 2018-2022) - Al Hazmi, Raldin Alif (Educoretax, 2024)
A company is established to earn profits and in the long run to maximize the value of the company. Satisfactory company performance in the market will attract investors and potential investors and will increase company value. This study aims to determine and examine the effect of tax avoidance, profitability and company size on firm value in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. Data obtained from www.idx.com, the company's official website, and www.finance.yahoo.com. Sample data based on purposive sampling, using 8 companies listed on the IDX with a total sample of 40 sample data. Hypothesis testing is done with multiple linear regression analysis for panel data. The test results conducted in this study found that tax avoidance has no effect on firm value, profitability affects firm value, and company size has no effect on firm value. This research is expected to add to the literature for users of financial statements and investors and to be able to better utilize their resources and further maximize company profits.